Inovasi Produk Kopicek (Kopine Wong Picek) Sebagai Upaya Pemberdayaan Kelompok Difabel Tunanetra Mata Hati - Pradana, Bagus Cahyo Shah Adhi; Farhanindya, Hikmah Husniyah; Ardiana, I Dewa Ketut Raka (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Coffee is an important commodity with significant global demand. In Indonesia, East Java Province contributed 85.15% of the national coffee production in the Large Estate sector in 2022, supporting the growth of the local coffee industry such as coffeeshops. In Surabaya, the Mata Hati Community, consisting of people with disabilities, launched a coffee brand called